Self-Esteem dan Optimisme Hubungannya dengan Subjective Well-Being Remaja Panti Sosial Asuhan - Farhatunni’mahFarhatunni’mah; Rahayu, Anizar (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2025)
This study aims to determine the relationship between self-esteem and optimism with subjective well- being of adolescents in social care institutions in Jakarta. This study uses quantitative methods, with 3 research instruments, namely subjective well-being based on Diener’s theory (2009), self-esteem based on Tafarodi and Swann’s theory (2001) and optimism based on Seligman (2008). The sample of this study amounted to 158 adolescents. With the sampling technique using simple random sampling. Data were collected by questionnaire and analyzed using the JASP 0.18.3.0 program for Windows. The results of this study using the bivariate correlation method show that there is a significant relationship with a positive direction between self-esteem towards the subjective wellbeing of adolescents in social orphanages in Jakarta with a correlation coefficient (r = 0. 560 p = <0.001 (<0.05)), there is a significant relationship with a positive direction between optimism towards the subjective well-being of adolescents in social orphanages in Jakarta based on the results of the coefficient (r = 0.231 with p = 0.003 (<0.05)). Based on the results of the analysis using the multivariate Correlation enter method, the R value is 0.536 and R 2 is 0.288 with p = <0.001 (<0.05)). This shows that there is a significant relationship between self-esteem and optimism towards the subjective well-being of adolescents in social care institutions in Jakarta by 28.8%. Based on multivariate correlation stepwise, the contribution of self-esteem to the formation of subjective well-being is 28.7% while optimism contributes 0.1%.